Stable isotope probing and related technologies - Murrell, J. C.; Whiteley, Andrew S. (ASM Press, 2011)
"Stable isotopes, isotopes that are non-reactive, are chemically very similar and thus their behavior is close to identical, but fractionation technologies can separate the isotopes because of their different mass. They have been used for a number of years in botanical studies, but more recently stable isotopes-chiefly oxygen, nitrogen and carbon- have been used in ecological and climate studies. This volume contains chapters by leading researchers in microbial ecology who have been using and developing stable isotope technology, often in combination with genomics. It offers a timely look at the use of stable isotopes in many microbial ecology applications, which has ballooned in the last few years."--Pub. desc.
Keywords: Molecular probes.; Stable isotope tracers.; elektronické knihy; electronic books